For-Giving Death: Cixous's Osnabrück and Le Jour où je n'étais pas là - Eilene Hoft-March (Studies in 20th & 21st Century Literature, 2004)
In her early writings, Hélène Cixous earned recognition as the feminist proponent of a theory of gift economy that challenges the patriarchal practice of giving. Patriarchal giving, she contended, enacts the master-slave dialectic, maintaining power differentials by indemnifying and reducing the other to the one who gives. Cixous imagined an alternate practice whereby the gift incurs no debts and no death for the other, a giving without expectation of return, a generosity that enriches all who participate. More than two decades after those theoretical essays, Cixous continues to explore in her fiction the relationship to the other as mediated by gifts; however, her earlier concept of giving has been considerably modified, as a reading of two very recent novels will show. In Osnabrück, an otherwise admirable model of generosity is put in question for ignoring the debts and death that dog even the most generous relationships with the other. Extending this understanding, Le Jour où je n'étais pas là presents death and debt as non-negotiable givens and obliges us to conceive of a kind of generosity predicated simultaneously on death and on the forgetting of death.
Keywords: Hélène Cixous; feminist; feminism; patriarchal; patriarchy; challenges patriarchy; giving; patriarchal giving; master-slave dialectic; power; power structures; debt; death; Osnabrück; Le Jour où je n& #x27; étais pas là; forgetting of death